2016
DOI: 10.3389/fimmu.2016.00240
|View full text |Cite
|
Sign up to set email alerts
|

The Mucosal Immune System and Its Regulation by Autophagy

Abstract: The gastrointestinal tract presents a unique challenge to the mucosal immune system, which has to constantly monitor the vast surface for the presence of pathogens, while at the same time maintaining tolerance to beneficial or innocuous antigens. In the intestinal mucosa, specialized innate and adaptive immune components participate in directing appropriate immune responses toward these diverse challenges. Recent studies provide compelling evidence that the process of autophagy influences several aspects of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 344 publications
(422 reference statements)
1
75
0
1
Order By: Relevance
“…Initial links between autophagy and host immunity came from the observations that autophagy can target intracellular bacteria for degradation. However, subsequent studies indicated that autophagy plays a much broader role in immune responses, as it can impact antigen processing, thymic selection, lymphocyte homeostasis and the regulation of immunoglobulin and cytokine secretion …”
Section: Linkage and Genome Wide Association Studiesmentioning
confidence: 99%
“…Initial links between autophagy and host immunity came from the observations that autophagy can target intracellular bacteria for degradation. However, subsequent studies indicated that autophagy plays a much broader role in immune responses, as it can impact antigen processing, thymic selection, lymphocyte homeostasis and the regulation of immunoglobulin and cytokine secretion …”
Section: Linkage and Genome Wide Association Studiesmentioning
confidence: 99%
“…Autophagy is a popular self-protective mechanism, the function of which mainly relies on lysosome. There is much evidence to suggest that autophagy could effectively attenuate the over-triggering of several self-defensive pathways such as inflammatory reaction and immune responses (46). Based on the statement, autophagy has been increasingly studied by researchers for the development of novel and effective therapeutic strategies against inflammation- or immune-related disorders, including IBD.…”
Section: Introductionmentioning
confidence: 99%
“…The GI tract, specifically the intestine, comprises the largest component of the immune system and is home to various populations of immune cells including antigen presenting dendritic cells (DCs) and macrophages as well as large populations of T cells and B cells, making the oral mucosa an attractive target for delivering DNA vaccines [15,16]. Oral DNA vaccination can also generate mucosal immune responses, providing important first line protection against pathogens invading at mucosal sites [17].…”
Section: Oral Gene Delivery For Dna Vaccinationmentioning
confidence: 99%